Perkuatan Ikatan Plastik dan Matriks Semen Menggunakan Metode Soybean Crude Urease - Calcite Precipitation (SCU-CP) - Heriansyah Putra; Rizki Amelia (Jurnal Teknik Sipil, 2022)
Plastic is widely used because it is light, strong, and stable. However, plastic will produce waste that is difficult to decompose. One effective way to manage plastic waste is to recycle it into plastic pellets. Besides being used as a raw material for making recycled plastic, plastic pellets can be used as a substitute for fine aggregate. The compressive strength test of plastic concrete decreases compressive strength. It is due to plastic’s slippery surface, which weakens the bond between plastic and cement matrix. Calcite deposition using Soybean Crude Urease Calcite Precipitation (SCU-CP) method is expected to provide a solution. This study discussed the effect of High-Density Polyethylene (HDPE) plastic pellets on concrete strength as the fine aggregate substitution. In addition, the impact of calcite on concrete with HDPE plastic substitution was also evaluated in this study. The results show that plastic substitution decreases the strength of concrete. On the other hand, adding calcite can improve compressive strength compared to plastic concrete without SCU-CP. The optimum compressive strength was obtained with a variation of 1% plastic and 5% SCU-CP, which increased 7.5% and 2.8% higher compared to the normal concrete and plastic concrete without calcite, respectively. This study elucidated that the adding SCU-CP method to plastic concrete has a great potential to optimize the concrete strength.